THE ROLE AND STRUCTURE OF EDUCATIONAL COMPONENT IN PHD PROGRAMS OF A NEW TYPE - Boris I. Bednyi (Moscow Polytechnic University, 2022)
The article presents an analysis of the main trends in the development of doctoral educationin the framework of the Bologna process. Practical experience of modernizing the system for academic staff training in the postgraduate school of Lobachevsky State University of Nizhni Novgorod is summarized.